Solve for y x-y=13

Math
x-y=13
Subtract x from both sides of the equation.
-y=13-x
Multiply each term in -y=13-x by -1
Tap for more steps…
Multiply each term in -y=13-x by -1.
(-y)⋅-1=13⋅-1+(-x)⋅-1
Multiply (-y)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1y=13⋅-1+(-x)⋅-1
Multiply y by 1.
y=13⋅-1+(-x)⋅-1
y=13⋅-1+(-x)⋅-1
Simplify each term.
Tap for more steps…
Multiply 13 by -1.
y=-13+(-x)⋅-1
Multiply (-x)⋅-1.
Tap for more steps…
Multiply -1 by -1.
y=-13+1x
Multiply x by 1.
y=-13+x
y=-13+x
y=-13+x
y=-13+x
Solve for y x-y=13

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top